Cyanovinylene-based copolymers synthesized by tin-free Knoevenagel polycondensation for high efficiency polymer solar cells. Issue 30 (17th July 2018) - Cao, Congcong; Xiao, Manjun; Yang, Xiye; Zhang, Jie; Huang, Fei; Cao, Yong
Abstract : Cyanovinylene-based copolymers were synthesized by a green, environmentally friendly, and tin-free Knoevenagel polycondensation and used in OPV devices as a donor material. A PCE of 8.54% was obtained with the device based on PdC8ThDT:ITIC. Abstract : A series of π-conjugated copolymers based on benzo[1, 2- b :4, 5- b ′]dithiophene (BDT) and cyanovinylene (CNV) moieties was synthesized by a green, tin-free Knoevenagel polycondensation and they were used as an electron donor for polymer solar cells. This synthetic method results in improved atom economy, the non-use of metal catalysts and the generation of only benign by-products. The relationship between the structure and performance was studied including the optical properties, electrochemical properties, thermal stability, morphologies and the performance in solar cells as donor materials. These copolymers showed broad absorption spectra in the UV-visible region and low-lying HOMO levels at about −5.50 eV due to the presence of the CNV unit. The open-circuit voltages ( V OC ) of the devices were near to 1.0 eV. A PCE of 8.54% was obtained with the device based on PdC8ThDT:ITIC due to the high hole mobility and excellent morphology of the active layer blend film.